Improving the Utilization of Isomaltose and Panose by Lager Yeast Saccharomyces pastorianus - Javier Porcayo Loza; Anna Chailyan; Jochen Forster; Michael Katz; Uffe Hasbro Mortensen; Rosa Garcia Sanchez (Fermentation, 2021)
Approximately 25% of all carbohydrates in industrial worts are poorly, if at all, fermented by brewing yeast. This includes dextrins, β-glucans, arabinose, xylose, disaccharides such as isomaltose, nigerose, kojibiose, and trisaccharides such as panose and isopanose. As the efficient utilization of carbohydrates during the wort’s fermentation impacts the alcohol yield and the organoleptic traits of the product, developing brewing strains with enhanced abilities to ferment subsets of these sugars is highly desirable. In this study, we developed Saccharomyces pastorianus laboratory yeast strains with a superior capacity to grow on isomaltose and panose. First, we designed a plasmid toolbox for the stable integration of genes into lager strains. Next, we used the toolbox to elevate the levels of the α-glucoside transporter Agt1 and the major isomaltase Ima1. This was achieved by integrating synthetic AGT1 and IMA1 genes under the control of strong constitutive promoters into defined genomic sites. As a result, strains carrying both genes showed a superior capacity to grow on panose and isomaltose, indicating that Ima1 and Agt1 act in synergy to consume these sugars. Our study suggests that non-GMO strategies aiming to develop strains with improved isomaltose and panose utilization could include identifying strains that overexpress AGT1 and IMA1.